Factorization of Hankel operators, range inclusion of Toeplitz and Hankel operators on the vector-valued Hardy space - Bhuia, Sudip Ranjan (Comptes Rendus. Mathématique)
Using Douglas theorem on factorization and range inclusion of bounded linear operators, we give the factorization of Hankel operators, range inclusion of Hankel and Toeplitz operators defined on vector-valued Hardy spaces.